Vers la ville de l’âge IV ? - Charles Ambrosino; Inès Ramirez-Cobo (Projets de Paysage)
The effects of climate change on human settlements are such that many experts are now urging urban planners not to rely solely on coercive preventive plans. A strict banning of building in areas prone to flooding no longer seems to be commensurate with the adaptability issues that weigh on urban developments and the methods used to design them. Current discussions regarding the notion of urban resilience have led, instead of the emergence of stringent regulatory frameworks, to the emergence of spatial systems and of projects that not only extend beyond the architectural dimension but also address the issue of risk management at the level of the region, the infrastructure and the landscape. While drawing on the results of an urban project workshop, we will endeavour to develop a theoretical hypothesis in line with the considerations made by Christian de Portzamparc on the three ages of the city. After having presented the postulate of a fourth age, that of “the adaptable city”, we will question the role of water in the configuration, design and construction of the contemporary city.